Analysis of the economic behavior of the actor using agency theory: theoretical analysis - OULAICH , Jamal (Revue Internationale des Sciences de Gestion, 2023)
The first economic analyzes of the organization, in particular, the analysis of relationships within the firm, encourage us to recall the work of Coase, in particular, on the question of the firm as an organization whose coordination be more efficient in relation to the market, by minimizing the costs that appear during an agency relationship. The variation in the value of costs is strongly linked to the behavior of the actors involved in the property transfer process in question. The analysis of the behavior of the internal actors of the organization from a cost point of view is done through the analysis of two major phenomena developed in this current. Firstly, the phenomenon of limited rationality, limiting the actor’s capabilities in calculating the profitability of these actions. Secondly, the opportunistic behavior of the actor, seeking to achieve his objectives by focusing on private interests. The objective of this research is the analysis of the economic behavior of actors, through agency theory.